Long-Term Efficacy and Safety of Zolpidem Extended-Release 12.5 mg, Administered 3 to 7 Nights Per Week for 24 Weeks, in Patients With Chronic Primary Insomnia: A 6-Month, Randomized, Double-Blind, Placebo-Controlled, Parallel-Group, Multicenter Study - Krystal, Andrew D. (Associated Professional Sleep Societies, LLC, 2008)
STUDY OBJECTIVES: To evaluate long-term efficacy and safety of zolpidem extended-release 3 to 7 nights/week for chronic primary insomnia. DESIGN: Multicenter, 25-week, phase IIIb, randomized, double-blind, placebo-controlled, parallel-group. SETTING: Outpatient; visits every 4 weeks. PATIENTS: Aged 18 to 64 years; DSM-IV criteria for chronic primary insomnia; ≥3 months of difficulty initiating or maintaining sleep or experiencing nonrestorative sleep. INTERVENTIONS: Single-dose zolpidem extended-release 12.5 mg (n = 669) or placebo (n = 349), self-administered from a minimum of 3 nights/week to a maximum of 7 nights/week. MEASUREMENTS AND RESULTS: Patient's Global Impression (PGI) and Clinical Global Impression-Improvement (CGI-I) were assessed every 4 weeks up to week 24. Patient Morning Questionnaire (PMQ), recorded daily, assessed subjective sleep measures—sleep onset latency (SOL), total sleep time (TST), number of awakenings (NAW), wake time after sleep onset (WASO), and quality of sleep (QOS)—and next-day functioning. At week 12, PGI, Item 1 (aid to sleep), the primary endpoint, was scored as favorable (i.e., “helped me sleep”) by 89.8% of zolpidem patients vs. 51.4% of placebo patients (P < 0.0001, based on rank score) and at week 24 by 92.3% of zolpidem extended-release patients vs. 59.7% of placebo patients. Zolpidem extended-release also was statistically significantly superior to placebo at every time point for PGI (Items 1–4) and CGI-I (P < 0.0001, rank score), TST, WASO, QOS (P < 0.0001), and SOL (P ≤ 0.0014); NAW (Months 2–6; P < 0.0001). Sustained improvement (P < 0.0001, all time points) was observed in morning sleepiness and ability to concentrate (P = 0.0014, month 6) with zolpidem extended-release compared with placebo. Most frequent adverse events for zolpidem extended-release were headache, anxiety and somnolence. No rebound effect was observed during the first 3 nights of discontinuation. CONCLUSIONS: These findings establish the efficacy of 3 to 7 nights per week dosing of zolpidem extended-release 12.5 mg for up to 6 months. Treatment provided sustained and significant improvements in sleep onset and maintenance and also improved next-day concentration and morning sleepiness. CITATION: Krystal AD; Erman M; Zammit GK; Soubrane C; Roth T. Long-Term Efficacy and Safety of Zolpidem Extended-Release 12.5 mg, Administered 3 to 7 Nights Per Week for 24 Weeks, in Patients With Chronic Primary Insomnia: A 6-Month, Randomized, Double-Blind, Placebo-Controlled, Parallel-Group, Multicenter Study. SLEEP 2008;31(1):79-90.